Efforts to Resolve Breach of Contract in Banking Credit Agreements (A Study of Decision No. 4/Pdt.G.S/2024/PN. Trt) - Pakpahan, Joel Fredly; Debora, Debora (Journal of Humanities Education Management Accounting and Transportation, 2025)
The granting of credit by banks to debtors is not solely based on trust but also adheres to the principle of prudence, taking into account the risks and feasibility of the debtor. One crucial step in credit agreements is the application of the 5C principles (Capacity, Capital, Character, Collateral, Condition), aimed at assessing the debtor's ability and suitability to fulfill their obligations. However, in the implementation of credit agreements, defaults or breaches of contract by debtors often occur, whether due to negligence, intentional actions, or force majeure. Defaults may include the debtor's inability to meet their debt obligations as agreed upon. To resolve this issue, two resolution pathways can be taken: litigation through the courts and non-litigation alternatives such as debt restructuring, rescheduling, and payment postponement. In court resolutions, simple lawsuit procedures are one of the methods used to handle default disputes efficiently. The case of default in the credit agreement between PT Bank Rakyat Indonesia and debtors Thamrin Simanjuntak and Riahta Sembiring illustrates the importance of the application of the principle of pacta sunt servanda in contractual agreements, where debtors are obligated to fulfill payment obligations as agreed. In cases of default, debtors are at risk of sanctions in the form of compensation in accordance with applicable legal provisions.